Targeting the integrated networks of aggresome formation, proteasome, and autophagy potentiates ER stress-mediated cell death in multiple myeloma cells - MORIYA, SHOTA; KOMATSU, SEIICHIRO; YAMASAKI, KAHO; KAWAI, YUSUKE; KOKUBA, HIROKO; HIROTA, AYAKO; CHE, XIAO-FANG; INAZU, MASATO; GOTOH, AKIHIKO; HIRAMOTO, MASAKI; MIYAZAWA, KEISUKE (International journal of oncology, 2015)
The inhibitory effects of macrolide antibiotics including clarithromycin (CAM) on autophagy flux have been reported. Although a macrolide antibiotic exhibits no cytotoxicity, its combination with bortezomib (BZ), a proteasome inhibitor, for the simultaneous blocking of the ubiquitin (Ub)-proteasome and autophagy-lysosome pathways leads to enhanced multiple myeloma (MM) cell apoptosis induction via stress overloading of the endoplasmic reticulum (ER). As misfolded protein cargo is recruited by histone deacetylase 6 (HDAC6) to dynein motors for aggresome transport, serving to sequester misfolded proteins, we further investigated the cellular effects of targeting proteolytic pathways and aggresome formation concomitantly in MM cells. Pronounced apoptosis was induced by the combination of vorinostat [suberoylanilide hydroxamic acid (SAHA); potently inhibits HDAC6] with CAM and BZ compared with each reagent or a 2-reagent combination. CAM/BZ treatment induced vimentin positive-aggresome formation along with the accumulation of autolysosomes in the perinuclear region, whereas they were inhibited in the presence of SAHA. The SAHA/CAM/BZ combination treatment maximally upregulated genes related to ER stress including C/EBP homologous protein (CHOP). Similarly to MM cell lines, enhanced cytotoxicity with CHOP upregulation following SAHA/CAM/BZ treatment was shown by a wild-type murine embryonic fibroblast (MEF) cell line; however, a CHOP-deficient MEF cell line almost completely canceled this pronounced cytotoxicity. Knockdown of HDAC6 with siRNA exhibited further enhanced CAM/BZ-induced cytotoxicity and CHOP induction along with the cancellation of aggresome formation. Targeting the integrated networks of aggresome, proteasome, and autophagy is suggested to induce efficient ER stress-mediated apoptosis in MM cells.